SLOW STROKE BACK MASSAGE SEBAGAI PENDEKATAN KEPERAWATAN DALAM MENURUNKAN NYERI PASIEN KANKER SERVIKS - Nelza Rahmadani; Fitri Dyna; Yureya Nita; Arlia Purwaningsih (SINERGI : Jurnal Riset Ilmiah, 2026)
Cervical cancer is one of the most common cancers affecting women in Indonesia. Management of cervical cancer generally involves chemotherapy, which often causes pain, especially in advanced stages. Approximately 50-70% of cervical cancer patients experience persistent pain. Unmanaged pain can decrease quality of life, limit daily activities, and cause psychological problems such as anxiety and depression, as well as physical disturbances including sleep problems and reduced appetite. Therefore, complementary non-pharmacological interventions are needed to support pain management. Slow Stroke Back Massage (SSBM) is a nursing intervention that promotes relaxation and reduces pain perception. This nursing care aimed to apply SSBM as an evidence-based nursing intervention to reduce pain in cervical cancer patients. The method used was a case study with the application of Evidence-Based Practice Nursing. The subject was a cervical cancer patient experiencing pain. The SSBM intervention was administered once daily for 3 consecutive days. Pain intensity was measured using the Numeric Rating Scale. The results showed that the average pain score before the SSBM intervention was 4, while after the intervention it decreased to 2. Patient observations indicated reduced pain intensity and increased comfort after the intervention. In conclusion, SSBM is an effective non-pharmacological pain